An overview on the synthesis of aluminium matrix composites using stir casting technique. (2022) - Singh, Kapil; Singh, Hartaj; Vardhan, Sachit; Mohan, Sanjay
Highlights: The stir casting route is the most suitable, and ease of handling and economical methodology to develop the composites. In this review article, the influence of particle embedment and the predominant factors attributed to mechanical stirring during the processing of aluminium matrix composites are explored. Furthermore, the recent development and various parameters and related constraints are also considered for improving the performance of AMC's to be achieved in the future are also to be detailed in this study. Abstract: Aluminum alloys are popular materials in industrial applications because of their higher specific strength to weight ratio and excellent mechanical properties. Various ceramics are added as reinforcement to improve mechanical characterizations of pure aluminum alloys and the newly synthesized material is recognized by aluminum matrix composites. Aluminum alloys have been used as matrix materials and materials such as aluminum oxide, magnesium oxide, boron carbide, silicon carbide, graphite, and fly-ash, and many more ceramics used as particulate reinforcements. The stir casting route is the most suitable, and ease of handling and economical methodology to develop the composites. In this review article, the influence of particle embedment and the predominant factors attributed to mechanical stirring during the processing of aluminum matrix composites are explored. Furthermore, the recent development and various parameters and related constraints that are also considered for improving the performance of aluminum matrix composites to be achieved in the future are also to be detailed in this study.